Advances in hybrid information technology : first international conference, ICHIT 2006, Jeju Island, Korea, November 9-11, 2006 ; revised selected papers - International Conference on Hybrid Information Technology; Szczuka, Maracin S. (Lecture Notes in Computer Science, 2007)
This book constitutes the thoroughly refereed post-proceedings of the First International Conference on Hybrid Information Technology, ICHIT 2006, held in Jeju Island, Korea, in November 2006. The 64 revised papers were carefully selected during a second round of reviewing and improvement from 235 reports given at the conference and are presented in extended version in the book. The papers are organized in topical sections on data analysis, modeling, and learning; imaging, speech, and complex data; applications of artificial intelligence; hybrid, smart, and ubiquitous systems; hardware and software engineering; as well as networking and telecommunications.